Effect of Care Support Treatment and Other Factors Affecting the Intention and Adherence to Antiretroviral Therapy: Path Analysis Evidence, from Malang East Java - Fitria Diyah Ayu Pangerti; Pawito Pawito; Hanung Prasetya (Masters Program in Public Health, Sebelas Maret University, 2019)
Background: People living with HIV/AIDS (PLWHA) are still a health problem because of the cumulative increase in the population and there is a gap in the need for services to get antiretroviral therapy (ART). Compliance with PLHIV will consume antiretroviral drugs is a form of treatment success by being influenced by several factors encouraging to act, attitudes, intentions, perceptions of behavioral control, and care, support and treatment services (CST). The purpose of this study was to analyze the effect of CST services and other factors that influence the intention and compliance of ARV therapy, using theory of planned behavior, health belief model, and path analysis.Subjects and Method: This was a cross sectional study conducted in Malang, East Java, from September to October 2019. A sample of 200 PLWH was selected by fixed disease sampling. The dependent variable was adherence to ARV treatment. The independent variables were intention, cues to action, attitude, perceived of behavioral control (PBC), and CST service. The data were collected by questionnaire and analyzed by path analysis run on Stata 13.Results: Adherence to ARV therapy in PLWH was directly increased by strong intention (b= 3.12; 95% CI= 2.12 to 4.12; p<0.001). CST service was directly increased adherence to ARV therapy, but it was statistically non-significant (b= 0.19; 95% CI= -0.89 to 1.28; p= 0.293). Adherence to ARV therapy was indirectly affected by strong cues to action, positive attitude, and strong PBC.Conclusion: Adherence to ARV therapy in PLWH is directly increased by strong intention. CST service is directly increased adherence to ARV therapy, but it is statistically non-significant. Adherence to ARV therapy is indirectly affected by strong cues to action, positive attitude, and strong PBC.Keywords: compliance, ARV therapy, PLWH, health belief model, theory of planned behavior Correspondence: Fitria Diyah Ayu Pangerti. Masters Program in Public Health. Universitas Sebelas Maret, Jl. Ir. Sutami 36A, Surakarta, Jawa Tengah, Indonesia, 57126. Email: ayupangerti13@yahoo.com. Mobile: 081332600710Journal of Health Promotion and Behavior (2019), 4(4): 298-305 https://doi.org/10.26911/thejhpb.2019.04.04.06